2007
DOI: 10.1183/09031936.00075806
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation during walking in patients with severe COPD: a randomised cross-over trial

Abstract: It was hypothesised that noninvasive positive-pressure ventilation (NPPV) applied during walking prevents exercise-induced hypoxaemia and improves exercise performance in severe chronic obstructive pulmonary disease (COPD) patients already receiving long-term NPPV.A total of 20 COPD patients (mean¡SD age 65.1¡8.7 yrs, forced expiratory volume in one second 27¡8% predicted and total lung capacity 116¡27% pred) reporting dyspnoea, even during mild exertion, underwent two 6-min walking tests with a rollator and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
7
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 34 publications
(63 reference statements)
3
98
7
9
Order By: Relevance
“…Furthermore, it has been reported that, in chronic hypercapnic COPD under long-term ventilatory support, high-intensity NPPV can also be administered during walking, with ventilator settings unchanged compared with those used at rest, resulting in improved oxygenation, decreased dyspnoea and increased walking distance. Therefore, NPPV during walking could prevent hypoxia-induced complications [95].…”
Section: Nppv As a Coadjuvant Of Prmentioning
confidence: 99%
“…Furthermore, it has been reported that, in chronic hypercapnic COPD under long-term ventilatory support, high-intensity NPPV can also be administered during walking, with ventilator settings unchanged compared with those used at rest, resulting in improved oxygenation, decreased dyspnoea and increased walking distance. Therefore, NPPV during walking could prevent hypoxia-induced complications [95].…”
Section: Nppv As a Coadjuvant Of Prmentioning
confidence: 99%
“…In this setting, oxygenation, dyspnea, and walking distance were substantially improved when NIV was added to supplemental oxygen. 79 One study on subjects with stable hypercapnic COPD directly compared the new concept of high-intensity NIV (mean IPAP 29 cm H 2 O) with the conventional approach using considerably lower IPAP (mean IPAP 15 cm H 2 O), which has been termed low-intensity NIV. 80 In this randomized crossover trial, the mean treatment effect between low-and high-intensity NIV, both used for 6 weeks at home, was Ͼ 9 mm Hg for nocturnal P aCO 2 , which served as the primary outcome, in favor of high-intensity NIV.…”
Section: High-intensity Niv In Copdmentioning
confidence: 99%
“…In addition, PAV increased endurance capacity more than the other interventions. More recently, a study by DREHER et al [9] showed that by applying high inspiratory pressures, the walking distance could be increased in patients with severe COPD. In this study, it was remarkable that the high inspiratory pressures needed by the patients during the night did not have to be adjusted during walking.…”
Section: Ventilatory Support During Exercise or Exercise Trainingmentioning
confidence: 99%